National Health Service Bill (memorandum)
1946-05-24 1946 1940s 6 pages -5- professional in composition, is to be set up. Any doctor in the Service who wishes to practice in a new area after the appointed day will require the Committee's consent. It should be noted that there is also positive provision for attracting doctors to under-doctored areas, by adjustments in remuneration scales. Statutory Health Committees (Fourth Schedule) Local health authorities will be required to appoint health committees, and refer to them all matters relating to the discharge of their functions under the Bill. They will have discretion to co-opt members who are not members of the authority. RESEARCH (Section 16) The Minister is empowered to conduct research, and to give financial aid to any person conducting research into any question relating to the prevention, diagnosis or treatment of illness or mental defectiveness. Regional Boards and Boards of Governors are also empowered to conduct research. We have previously expressed the view that a wide expansion of research work is imperatively necessary. We consider that this work should be co-ordinated with the National Service. Adequate records will have to be compiled to provide data for research. INDUSTRIAL HEALTH The Bill contains no provision for integrating the Industrial Health Service in the new National Service and we have expressed our disappointment at this important omission. We have been informed by the Minister that the Industrial Service will need considerable working out, and that to wait until this has been done would have meant delaying the main scheme. The Minister has however given an assurance that he intends to take the matter up at the first opportunity. In these circumstances it will be necessary for us in the meantime to press for improvements through the Ministry of Labour and other Departments concerned. AMBULANCE SERVICES (Section 27) So far as the ambulance service is concerned, we consider it undesirable that local authorities should be empowered to delegate their functions to voluntary organisations, and for this reason we recommend the deletion of Section 27 (2). Furthermore we do not consider that Section 27 provides for the complete inter-availability of ambulances between areas which is desirable. DENTISTS AND OCULISTS (a) Dentists (Section 40 and Summary page 12). Priority arrangements are to be made for expectant mothers and young people. Outside these arrangements, it will be the duty of Executive Councils to arrange with dentists in their area a general dental service. The object is to develop a general service in Health Centres or Dental Centres as quickly as possible, but the Summary emphasises that at first there may be delay. (b) Oculists (Section 41 and Summary Page 31). While under Part II of the Bill it is the Minister's duty to provide optical treatment and the supply of optical appliances as part of the hospital and specialist service, there is provision for a supplementary eye service to be arranged by Executive Councils while the full specialist eye clinic system is developing. This supplementary service can be wound up in any area when the 292/847/4/159